Probability, certainty and facts in Francis Bacon's Natural Histories : A double attitude towards Skepticism - Manzo, Silvia (2009)
Fil: Manzo, Silvia. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.